Market values for olive oil attributes in Chile: a hedonic price function. Issue 1 (5th January 2015) - Romo Muñoz, Rodrigo; Lagos Moya, Mario; Gil, José M.
Abstract : Purpose: – Focused on the olive oil sector in Chile which is a non-traditional market (both in production and consumption), the purpose of this paper is to determine the implicit value of the most relevant attributes of olive oil on the final price charged by supermarkets to consumers through the hedonic pricing methodology. Design/methodology/approach: – Field work was carried out between September and October 2012 in 12 supermarkets belonging to the four most important Chilean retail chains. A log-linear price-attribute function was used to estimate the hedonic price function. The sample included 248 observations olive oil prices available to consumers in the leading supermarkets in the city of Chillán (Chile). Findings: – The model estimation results led to the observation that the attributes that most positively influenced final price are oil acidity level, tin can container of imported oil, and origin. On the other hand, the attributes that most negatively influenced final consumer price are retailer house brand and plastic container. Research limitations/implications: – A limitation of this study is associated with the geographic area where it was carried out, that is, the city of Chillán in the Bío-Bío Region, which is the second largest region and accounts for 12 per cent of the total population. Further research should include other cities such as Santiago (capital), Concepción, Curicó and Valparaíso. Originality/value: – This study can be considered as a first approximation of a hedonic pricing model estimation for olive oil in non-traditional markets like Chile, which is considered an emerging market.